La aplicación del método Montessori y su influencia en la pre-lectura de las niñas y niños del primer año de educación básica de la unidad educativa trilingue “Inka Samana” del cantón Saraguro de la provincia de Loja, periódo 2012–2013 - Macas Morocho, Betty Luzmila (2015)
This research paper called: APPLICATION OF MONTESSORI METHOD AND ITS INFLUENCE ON THE PRE-READING THE CHILDREN FIRST YEAR BASIC EDUCATION EDUCATION UNIT TRILINGUAL "INKA SAMANA" SARAGURO OF CANTON Loja province, PERIOD 2012 -2013, the general object was: to analyze the influence of the application of Montessori method in developing skills with performance criteria in pre-reading children from the first year of basic education Trilingual education Unit "InkaSamana "Canton Saraguro 2012-2013. The following methods are used for the realization of the research: scientific; descriptive and analytic-synthetic techniques such as surveys for teachers and an observation guide for students. The population was formed of 20 children, 20 parents and 4 teachers. The analysis and interpretation of the data made use of statistical tables and graphic representations, and sources of scientific information for the interpretation of the results was also made. After processing the information the application of the Montessori method was established as the main conclusion whether it influences the development of skills with performance criteria, pre reading, the children from the first year of basic education Trilingual Education Unit "InkaSamana "Canton Saraguro school year 2012-2013., and other finding is that the use of low impact training material if in addressing some issues, it does not allow spark interest in children so if pre influences -reading, and a good performance in the classroom work.